1998
DOI: 10.1161/01.atv.18.6.870
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Plasma Viscosity and the Severity of Coronary Heart Disease

Abstract: Abstract-Several studies have indicated that plasma viscosity contributes to cardiovascular risk in men. So far, a significant relationship between plasma viscosity and the severity of coronary heart disease has not been found. Thus, the present study is the first to report on the relationship of plasma viscosity and the severity of coronary heart disease. In a collective of 1142 male myocardial infarction patients, plasma viscosity and additional laboratory parameters were determined. Atherosclerotic changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 42 publications
(30 reference statements)
1
38
0
2
Order By: Relevance
“…31 In a study involving 1142 male myocardial infarction patients, a positive relationship was found between plasma viscosity and the severity of coronary heart disease, even after adjusting groups for age, FBN and use of diuretics. 32 In our study, increased whole blood viscosity levels in Group 1 (the control group) were correlated to the elevated level of FBN in plasma. Although a lower FBN level was observed in Group 2 (the castration group), higher TC, TG, HDL-C and LDL-C levels might elevate the whole blood viscosity.…”
Section: Discussionsupporting
confidence: 54%
“…31 In a study involving 1142 male myocardial infarction patients, a positive relationship was found between plasma viscosity and the severity of coronary heart disease, even after adjusting groups for age, FBN and use of diuretics. 32 In our study, increased whole blood viscosity levels in Group 1 (the control group) were correlated to the elevated level of FBN in plasma. Although a lower FBN level was observed in Group 2 (the castration group), higher TC, TG, HDL-C and LDL-C levels might elevate the whole blood viscosity.…”
Section: Discussionsupporting
confidence: 54%
“…The use of diuretics may be associated with plasma viscosity. 25) However the serum level of UA was not associated with diuretics in high ABI group. It requires further investigation.…”
Section: Discussionmentioning
confidence: 79%
“…High plasma eWBV levels were displayed to cause an elevated risk of acute myocardial infarction (AMI) in patients with unstable angina pectoris. 31 Furthermore, an association of an early elevation in plasma viscosity during AMI and reinfarction or death was observed. Compared to patients with stable angina pectoris and healthy individuals, an increase in plasma viscosity was displayed in patients with severe unstable angina pectoris.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, in a previous study, the authors showed increased plasma eWBV levels in patients with stable angina pectoris even without coronary artery diseases. 31 The changes in eWBV levels have been showed in patients with cerebrovascular diseases. Plasma eWBV levels are elevated in patients with internal carotid atherosclerosis, independent of the presence of risk factors for CVD.…”
Section: Discussionmentioning
confidence: 99%